Early prodromal symptoms can predict future psychosis in familial high-risk youth - Tandon, Neeraj; Montrose, Debra; Shah, Jai; Rajarethinam, R.P.; Diwadkar, Vaibhav A.; Keshavan, Matcheri S. (Journal of psychiatric research, 2012)
Efforts to predict psychosis in individuals at high risk for schizophrenia have focused on the identification of sub-threshold clinical criteria and neurobiological markers, including neuropsychological assessment, structural and functional brain imaging, and psychophysiological testing. We sought to evaluate the relative utility of “psychosis-proneness” measures for prospective prediction of psychotic disorders in a group of young relatives at familial risk for schizophrenia. We examined the receiver operating characteristics of sub-threshold symptoms in predicting conversion to psychosis in a group of 97 young first- and second- degree relatives of persons with schizophrenia over a 2-year period. Towards this end, we utilized the Structured Interview of Prodromal Symptoms to derive measures of two of the four Scale of Prodromal Symptoms subscales (positive and disorganized) and the Chapman Magical Ideation and Perceptual Aberration scales. These four measures were, together, taken to reflect a putative index of psychosis-proneness. Eleven of the 97 subjects developed a psychotic disorder over 2 years of follow-up. Seventeen of the 97 subjects tested positive on this index of psychosis-proneness at baseline and of these 10 converted to psychosis. The sensitivity and specificity of the test were 91 percent and 92 percent respectively. The positive predictive value of the test was 59 percent and its negative predictive value was 99 percent. Addition of measures of cognitive or social function to the index decreased its predictive ability, reducing its specificity and/or sensitivity. A relatively simple set of clinical measures can be utilized to prospectively identify familial high risk individuals who convert to psychosis with high specificity and sensitivity. Implications for the proposed addition of an “Attenuated Psychosis Syndrome” in DSM-5 are discussed.